The Influence of Corporate Communication Strategy and Customer Value Creation Toward Creation of Reputation (Case Study) - Syaifuddin Syaifuddin (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2020)
The objectives of this research are to know and to analyze corporate communication strategy, customer value creation, creation of corporate reputation and the influence of corporate communication strategy and customer value creation toward creation of corporate reputation. This research is descriptive and verificative with descriptive survey and explanatory with stratified random sampling. The amount of sample is 55 respondents. Data collection techniques are library data, observation, and questioner. Analysis data used is path analysis. Research results show that the corporate communication strategy and customer value creation influence the creation of reputation Len Industri Group is 53.7% simultaneously. The influence of corporate communication strategy to the creation of reputation is at 47.2% partially whereas the customer value creation does not significantly influence the creation of reputation is 5.1%.